Effect of Process Parameters on the Mechanical Properties of Simultaneous Double-Sided Friction Stir Welding Joints - Shaofei Meng; Huihui Zhao; Jiyi Dong; Wu Liu; Haitao Liu; Juliang Xiao (Chinese Journal of Mechanical Engineering, 2024)
Abstract Currently, conventional single-sided friction stir welding is primarily suitable for joining thin plate aluminum alloys, and its application to thick plates is still challenging in terms of welding efficiency and joint mechanical properties. Simultaneous double-sided friction stir welding (SDS-FSW) is a high-efficiency joining technique specifically developed for welding thick plates. However, there is little research on the influence of SDS-FSW process parameters on the joint mechanical properties. In this study, a 12 mm thick AA6061-T6 aluminum alloy and dual robot welding equipment are used to conduct SDS-FSW experiments exploring the influence of rotational speed $$ω$$ ω and welding speed v on the mechanical properties and microstructure. The results show that when the welding parameters are $$ω$$ ω = 800 r/min and v = 60–80 mm/min, smooth and defect-free thick plate aluminum alloy SDS-FSW joints can be obtained, and the macroscopic morphology of the joints is distributed in a “dumbbell” shape. The grain size in the weld nugget zone increases with increasing welding heat input. The microhardness distribution in the joint displays a “W” shape, and the hardness value of the weld nugget zone can reach 67% to 86% of that of the base metal (BM). The junction between the thermo-mechanically affected zone and the heat affected zone is the weakest region of the joint, with the lowest hardness being approximately 51% of that of the BM. When the welding parameters are $$ω$$ ω = 800 r/min and v = 140 mm/min, the SDS-FSW joint has the highest tensile strength, reaching 78.43% of the BM strength and exhibiting ductile fracture characteristics. This research indicates that acceptable weld strength in thick aluminum alloys can be achieved via the SDS-FSW joining mechanism, highlighting its significant potential for industrial applications.